Hayek in Mind : Hayek's philosophical psychology - Marsh, Leslie (Advances in Austrian economics, 2011)
The volume gathers together papers presented at the second biennial Wirth conference on Austrian economics, held in October 2008 when the crisis of Fall 2008 was still new and shocking. This coincidence of timing makes policy issues and crisis management a kind of leitmotif of the volume.